Macroeconomic Development and Stock Market Performance: A Non-Parametric Approach - George Adu; George Marbuah; Justice Tei Mensah; Prince Boakye Frimpong (Economics and Econometrics Research Institute (EERI), 2013)
This paper applies a local-linear non-parametric kernel regression technique to examine the effect of macroeconomic factors on stock market performance in Ghana. We show that the popular parametric specification in the existing literature suffers from functional misspecification. The evidence suggests that the relationship is non-linear and hence the implied elasticities are non-constant, contrary to findings in the literature. The main finding of the study suggests that stock prices are significantly affected by macroeconomic fundamentals and oil price shocks albeit weakly. This reinforces the need to closely monitor behaviour of macroeconomic indicators while sustaining prudent macroeconomic policy management.
Keywords: C13; C14; G00; O55; 330; Bandwidth; Ghana stock exchange; local-linear kernel regression; nonparametric